Developmental Trajectories of Early Higher‐Order Thinking Talk Differ for Typically Developing Children and Children With Unilateral Brain Injuries. Issue 2 (5th October 2021) - Frausel, Rebecca R.; Vollman, Elayne; Muzard, Antonia; Richland, Lindsey E.; Goldin‐Meadow, Susan; Levine, Susan C.
ABSTRACT: The use of higher‐order thinking talk (HOTT), where speakers identify relations between representations (e.g., comparison, causality, abstraction) is examined in the spontaneous language produced by 64 typically developing (TD) and 46 brain‐injured children, observed from 14–58 months at home. HOTT is less frequent in lower‐income children and children with brain injuries, but effects differed depending on HOTT complexity and type of brain injury. Controlling for income, children with larger and later‐occurring cerebrovascular infarcts produce fewer surface (where relations are more perceptual) and structure (where relations are more abstract) HOTT utterances than TD children. In contrast, children with smaller and earlier occurring periventricular lesions produce HOTT at comparable rates to TD children. This suggests that examining HOTT development may be an important tool for understanding the impacts of brain injury in children. Theoretically, these data reveal that both neurological (size and timing of brain injury) and environmental (family income) factors contribute to these skills. LAY ABSTRACT: We examined talk produced by 1‐ to 5‐year‐old children going about their everyday routines. Some children had experienced early brain injuries, and we compared their talk to the talk of typically developing children, to better understand how brain injury may affect language and thinking abilities. Children with brain injuries generally expressed less complex thinking in their talk (e.g., they compared how things look, as opposed to how things work), which may impact their school readiness and success.